EDUKASI PEMAKAIAN PLASTIK SEBAGAI KEMASAN MAKANAN DAN MINUMAN SERTA RISIKONYA TERHADAP KESEHATAN PADA MASYARAKAT - Robertus Suraji; Istianingsih (Jurnal Abdimas Ekonomi dan Bisnis (JAmEB), 2022)
The largest source of waste is from settlements, the composition is 75% consisting of organic waste and only 25% inorganic waste. Organic waste has been widely used as material for making compost, briquettes and biogas, but inorganic waste is still very poorly managed. Inorganic waste is very difficult to be degraded and even cannot be degraded at all by nature, therefore a very large area is needed to compensate for the production of this type of waste. The most common inorganic waste found in the community is plastic waste. In 2018 the production of plastic waste for packaging reached 925,000 tons and about 80% of it has the potential to become waste that is harmful to the environment. Exposure to additives in plastics (plasticizers) has a wide impact on health, especially for the fetus and child. Plastics are widely used as food and beverage packaging. Knowing how to choose and use the right type of plastic that will come into contact with food is important to avoid the risk of exposure to harmful chemicals in plastic. This service program aims to educate about the impact of plasticizers on health through public education programs targeted at community leaders around the Bhayangkara University, Jakarta Raya Bekasi. Education is delivered in the local language and is followed by free discussion with participants via virtual. Response analysis showed that most of the participants did not know how to use plastic properly as food and beverage packaging and did not know the classification of plastics. However, most agree that the use of plastics should be limited in food processing and that children are susceptible to the dangers of plasticizers. Educational results show a change in participant responses. It was concluded that this educational program effectively modified participants' attitudes and knowledge about the risks of using plastic in the processing and packaging of food and beverage products. Keywords: education, health, food, beverage, plastic